DESENVOLVIMENTO DE UM CONVERSOR A/D INTEGRADOR COM FAIXA DE ENTRADA E RESOLUÇÃO PROGRAMÁVEL A CAPACITOR CHAVEADO - Bezerra, Thiago Brito (2012)
Programmable integrated circuits enable its adjustment after fabrication to fit more than one application within a certain set of applications. A programmable measurement system can be applied to the measurement of different quantities involving a set of sensors with different signal characteristics and employing a single analog-to-digital converter (ADC). The output signal range for each sensor should be adjusted to be as close to the input range of the ADC as possible, to ensure maximum measurement quality. One solution to implement the adjustment on the signal range is the use of a measurement system with programmable conditioning circuit. In this work, it is proposed to design an ADC integrated circuit whose input range is adjusted to the signal level at the output of the sensor in order to avoid amplification stages in a signal conditioning circuit. For this adjustment, the input of the converter should be programmable, making it more compatible with various sensors with different characteristics. The developed ADC also allows the configuration of the converter resolution, enabling the designer to exploit trade-offs between resolution and conversion speed for a given application. The ADC is a switched capacitor integrating converter and it was designed for the AMS 0.35 μm CMOS process.